Outdoor sunlight-driven scalable water-gas shift reaction through novel photothermal device-supported CuOx/ZnO/Al2O3 nanosheets with a hydrogen generation rate of 192 mmol g−1 h−1. Issue 37 (15th September 2020) - Shi, Chengcheng; Yuan, Dachao; Ma, Luping; Li, Yaguang; Lu, Yangfan; Gao, Linjie; San, Xingyuan; Wang, Shufang; Fu, Guangsheng
Abstract : A new photothermal device is constructed by the Cr based selective light absorption film which can heat the 2D CuZnAl to 297 °C under 1 standard sun irradiation, leading to a 192 mmol g −1 h −1 of H2 production rate from 1 sun irradiated WGS reaction. Abstract : Hydrogen generation from water-gas shift (WGS) reaction requires the import of secondary energy, making it unsuitable for large scale applications. Herein, we present a new scalable system consisting of new photothermal device and catalysts that can produce hydrogen via the WGS reaction with zero additional energy import. The new photothermal device based on a chromium film can completely absorb sunlight, fully convert sunlight to heat energy and localize the heat energy synergistically, which makes a high temperature of 305 °C under one standard sunlight irradiation. The catalysts are scalable CuO x /ZnO/Al2 O3 nanosheets (2D CuZnAl) with high WGS activity, which were synthesized via the surfactant effect of boric acid. The 2D CuZnAl could be heated to 297 °C under one standard solar irradiation with the new photothermal device. This new system shows a hydrogen production rate of 192.33 mmol g −1 h −1 under one standard sunlight irradiation, 402 times to that of the current record of the one sunlight-driven WGS reaction. Moreover, this new system could be amplified to industrial scale with 4.2 m 2 of irradiated area and was able to generate 6.60 m 3 of hydrogen from the WGS reaction solely driven by outdoor sunlight in the daytime of spring as well as realized a zero emission of CO2 with the help of a greenhouse agriculture. This study introduces a scalable, highly efficient zero CO2 emission and stable route of outdoor sunlight-driven hydrogen generation from the WGS reaction.